2003
DOI: 10.1016/s1044-0305(03)00478-1
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation studies of noncovalent sugar-sugar complexes by infrared atmospheric pressure MALDI

Abstract: An investigation of sugar-sugar noncovalent complex fragmentation was conducted using a 2.94 m Er:YAG laser for infrared (IR) atmospheric pressure matrix-assisted laser desorption/ ionization (AP MALDI) on an ion trap mass spectrometer (ITMS). This approach allowed the analysis of weak noncovalent complexes between a variety of biologically relevant oligosaccharides. The strength of interaction varied with different sugar structures, potentially due to varying strength of hydrogen bonding networks. In some cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…The coupling AP-IR-MALDI will be surely the method of choice in the next few years. It has already been demonstrated that it is a powerful technique for the study of sugar non-covalent complexes [141].…”
Section: Resultsmentioning
confidence: 99%
“…The coupling AP-IR-MALDI will be surely the method of choice in the next few years. It has already been demonstrated that it is a powerful technique for the study of sugar non-covalent complexes [141].…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to consider the effect of sugar concentration on peptide–sugar complex formation. Previous work demonstrated that sugars containing sialic acid have the ability to form strong non‐covalent homodimers and homopolymers 29. The presence of high concentrations of 3′SL and 6′SL results in a strong signal from sugar monomer and sugar dimers, trimers and tetramers (data not shown).…”
Section: Resultsmentioning
confidence: 80%
“…Earlier work involving sugar–sugar complexes demonstrated the effectiveness of IR AP‐MALDI as a technique to study non‐covalent interactions 29. The stabilization of weak interaction by ambient gases following ionization allowed for CID testing of the strength of interaction between several oligosaccharides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a bifunctional guest can potentially offer combined acid and base catalysis for glycosidic bond cleavage. During the course of our work, Von Seggern and Cotter have reported that non-covalent sugarsugar complexes also undergo sugar fragmentation and rearrangement before complex breakdown, although they did not offer mechanistic insights into these processes [6]. Anionic complexes between chloride ions and oligosaccharides also appear to facilitate cleavage of saccharide bonds [7].…”
mentioning
confidence: 94%